Factors associated with adherence to low protein diet among patients with stage III-V of chronic kidney disease in an outpatient clinic at Hospital Pakar Sultanah Fatimah - Leong, Sim Kian (Universiti Putra Malaysia Press, 2020)
Introduction: Although the benefit of low protein diet (LPD) on chronic kidney disease (CKD) progression is well documented, patients’ adherence remains as the main challenge. Therefore, this study sought to identify adherence towards LPD among CKD patients and determine possible associating factors. Methods: This cross-sectional study was done at the Hospital Pakar Sultanah Fatimah in Muar, Johor, among stage III to V CKD patients. Three-day dietary recalls were used to quantify dietary energy (DEI) and protein intake (DPI). Factors investigated include socio demographic characteristics, medical history, anthropometry and body composition measurements, dietary knowledge, appetite level, handgrip strength, perceived stress, and health locus of control. Associating variables were analysed with logistic regression analysis. Results: The final analysis included 113 patients (54% male) with a mean estimated glomerular filtration rate of 17.5±11.2mL/min/1.73m2 and the average age of 56.3±12.8 years. Mean DEI and DPI were 22.4±5.9kcal/kg/day and 0.83±0.28g/kg/day, respectively. Only 34.5% of patients adhere to the LPD diet with 59% exceeding the DPI recommendation. Poorer LPD adherence was associated with longer duration of hospitalization (OR 0.707, 95%CI 0.50-1.00, p=0.048), higher energy intake (OR 0.744, 95%CI 0.65-0.85, p<0.001), advance CKD stage (OR 0.318, 95%CI 0.13-0.77, p=0.012) and having better dietary knowledge (OR 0.380, 95%CI 0.17- 0.85, p=0.018). Conclusion: LPD adherence of CKD patients in our institution is very poor signifying the need for engagement at the earlier stage of CKD to identify and stratify the patients for a targeted dietary intervention.